Human Resource Management in Employee Performance Measurement and its Influence on Guest Satisfaction at Mercure Hotel Padang - Praci, Rusti Mawa; Yuliana, Yuliana (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The hospitality industry is a sector that relies heavily on the quality of human resources (HR) to provide excellent service and create a positive experience for guests. This article discusses the important role of HR in the hospitality industry, examines theories related to HR management, and the factors that affect employee performance. Some of the theories discussed include human resource management theory, Maslow's motivation theory, transformational leadership theory, and human resource development theory through training and competence. In addition, this article also identifies the challenges faced in HR management, such as the high rate of employee turnover and the need for special skills. Through effective human resource management, hotels can improve service quality, create a productive work environment, and achieve sustainable competitive advantage. This study provides important insights for hotel managers to optimize the potential of human resources as a strategic asset in achieving organizational goals.